Transition Metal Selenides for Electrocatalytic Hydrogen Evolution Reaction - Feng, Wenshuai; Pang, Wenbin; Xu, Yan; Guo, Aimin; Gao, Xiaohui; Qiu, Xiaoqing; Chen, Wei (ChemElectroChem, 2020)
Electrolysis of water is regarded as an attractive and feasible way for producing hydrogen. So far, various non‐noble metal nanomaterials have been reported as excellent electrocatalysts for hydrogen evolution reaction. Especially, due to the low cost, earth‐abundance and tunable properties, transition metal selenides with different compositions, sizes and structures have been explored broadly as efficient catalysts with the relatively high activities, high stabilities and high efficiencies in full pH range of electrolyte for electrochemical hydrogen evolution reaction. Thus, in this Minireview, after introducing several commonly used electrochemical terms about hydrogen evolution reaction, we mainly focus on various kinds of the transition metal selenides that have been documented as electrocatalysts for hydrogen evolution reaction. Particularly, the merits and demerits of transition metal selenides for hydrogen evolution reaction are systematically discussed. Moreover, we also analyze the encountered challenges and present an outlook for the rapid development of transition metal selenides. We hope this Minireview can bring some fundamental understanding for the readers interested in the transition metal selenides and hydrogen evolution reaction. Abundant and efficient: Thanks to low cost, earth‐abundance, and tuneable properties, transition metal selenides (TMSs) have been explored as efficient catalysts for electrochemical hydrogen evolution reaction. The advances of the synthesis methods, physical and chemical properties of TMSs for electrocatalysis in hydrogen production has been summarized in this Minireview. Moreover, the application and perspective for TMSs in electrocatalytic hydrogen evolution reaction, including single‐metal selenides and multi‐metal selenides, have been discussed systematically.